Surface crack detection and monitoring in metal structure using RFID tag. Issue 1 (13th January 2020) - Xu, Yawei; Dong, Lihong; Wang, Haidou; Xie, Xiaozhu; Wang, Peng
Abstract : Purpose: RFID tags for sensing are available to operate and transmit sensing data to measurement equipment without battery and wires, which is a great advantage in establishing IoT environment. For crack sensing tags, however, the short service life of tags restricted their application. This paper aims to introduce a method of surface crack detection and monitoring based on RFID tag, which makes it possible for tags to be reused. Design/methodology/approach: Metal plate to be monitored, acting as the ground plane of microstrip patch antenna, is underneath the crack sensing tag. The propagating surface crack in metal plate will change the electric length of tag's antenna that is directly proportional to the crack depth and length. Thus, the deformation of sensing tag introduced by the load on metal structure is no longer a prerequisite for crack sensing. Findings: The simulated and experimental results show that the proposed crack sensing tag can sense the change of surface crack with mm-resolution and sense surface crack propagation without a deformation, which means the proposed crack sensing tag can be reused. Originality/value: The key advantage of the proposed method is the reusability of the RFID tags.